The ethanolic extract from Erythrina mulungu Benth. flowers attenuates allergic airway inflammation and hyperresponsiveness in a murine model of asthma. (5th October 2019) - Amorim, Jowanka; Borges, Marcos de Carvalho; Fabro, Alexandre Todorovic; Contini, Silvia Helena Taleb; Valdevite, Mayara; Pereira, Ana Maria Soares; Carmona, Fabio
Abstract: Ethnopharmacological relevance: Erythrina mulungu Benth. ("mulungu", Fabaceae) is a Brazilian native species with ethnopharmacological use for respiratory diseases. However, the effects of E. mulungu on the respiratory were never studied. Aims of the study: To evaluate the effects of an ethanolic extract from flowers of E. mulungu in ovalbumin (OVA)-induced asthma in mice, and to study the mechanisms involved. Materials and methods: OVA-sensitized mice were intraperitoneally (i.p.) treated with four doses (200, 400, 600, and 800 mg/kg) of the E. mulungu extract or dexamethasone (DEXA, 2 mg/kg) during seven consecutive days and simultaneously challenged with intranasal OVA. Bronchial hyperresponsiveness was evaluated in vivo, 24 h after the last OVA challenge. Bronchoalveolar lavage (BAL) was collected for counting the number of total and differential inflammatory cells. Blood was collected for measurement of anti-OVA IgE levels. Levels of cytokines interleukin (IL)− 4, IL-5, IL-10, IL-13, and interferon (INF)-γ were measured in pulmonary homogenate by ELISA. The recruitment of inflammatory cells to the lung tissue was determined using hematoxylin and eosin staining (H&E). The extract's chromatographic profile was evaluated by ultra-performance liquid chromatography-mass spectrometry (UPLC-MS). Results: The treatment with E. mulungu extract significantly reduced bronchial hyperresponsiveness, significantly reduced the number of leukocytes, eosinophils, and lymphocytes in BAL, and significantly decreased the levels of IL-4 and IL-5, while increased levels of IL-13 and INF-γ. In addition, E. mulungu significantly decreased the cellular inflammatory infiltration in the lung tissue. Erysotrine, erysotrine- N -oxide, and hypaphorine were the major constituents identified in the extract. Conclusion: Collectively, these results confirm the potential of E. mulungu for asthma treatment, through modulation of inflammatory response, supporting its ethnopharmacological use for respiratory diseases. Graphical abstract: fx1